Arthur's TV trouble - Brown, Marc Tolon (Boston : Little, Brown, 1995)
When Arthur sees advertisements for the amazing doggy Treat Timer, he decides to earn enough money to buy it for his dog Pal.
Elem. School Library Collection.
School Library Journal.
Booklist.
2.5
K-3
Keywords: Advertising -- Fiction; Money-making projects -- Fiction; Brothers and sisters -- Fiction; Aardvark -- Fiction; Arthur (Fictitious character : Brown) -- Fiction; Advertising -- Fiction; Money-making projects for children -- Fiction; Aardvarks -- Fiction; Siblings -- Fiction; Arthur (Fictional character : Brown) -- Fiction; Advertising -- Fiction; Moneymaking projects -- Fiction; Brothers and sisters -- Fiction; Aardvark -- Fiction